Upgrading a microplate reader for photobiology and all-optical experiments. Issue 2 (6th November 2014) - Richter, Florian; Scheib, Ulrike S.; Mehlhorn, Jennifer; Schubert, Roman; Wietek, Jonas; Gernetzki, Oliver; Hegemann, Peter; Mathes, Tilo; Möglich, Andreas
Abstract : Using open-source electronics and optical components, we add programmable illumination capabilities to a multimode microplate reader, thus enabling photobiological and all-optical experiments at high throughput, reproducibility and fidelity. Abstract : Automation can vastly reduce the cost of experimental labor and thus facilitate high experimental throughput, but little off-the-shelf hardware for the automation of illumination experiments is commercially available. Here, we use inexpensive open-source electronics to add programmable illumination capabilities to a multimode microplate reader. We deploy this setup to characterize light-triggered phenomena in three different sensory photoreceptors. First, we study the photoactivation of Arabidopsis thaliana phytochrome B by light of different wavelengths. Second, we investigate the dark-state recovery kinetics of the Synechocystis sp. blue-light sensor Slr1694 at multiple temperatures and imidazole concentrations; while the kinetics of the W91F mutant of Slr1694 are strongly accelerated by imidazole, the wild-type protein is hardly affected. Third, we determine the light response of the Beggiatoa sp. photoactivatable adenylate cyclase bPAC in Chinese hamster ovary cells. bPAC is activated by blue light in dose-dependent manner with a half-maximal intensity of 0.58 mW cm −2 ; intracellular cAMP spikes generated upon bPAC activation decay with a half time of about 5 minutes after light switch-off. Taken together, we present a setup which is easily assembled and which thus offers a facile approach to conducting illumination experiments at high throughput, reproducibility and fidelity.